Water use efficiency responses to fluctuating soil water availability in contrasting commercial sugar beet varieties - Barratt, Georgina E.; Murchie, Erik H.; Sparkes, Debbie L. (Frontiers in Plant Science, 2023)
Many areas of sugar beet production will face hotter and drier summers as the climate changes. There has been much research on drought tolerance in sugar beet but water use efficiency (WUE) has been less of a focus. An experiment was undertaken to examine how fluctuating soil water deficits effect WUE from the leaf to the crop level and identify if sugar beet acclimates to water deficits to increase WUE in the longer term. Two commercial sugar beet varieties with contrasting upright and prostrate canopies were examined to identify if WUE differs due to contrasting canopy architecture. The sugar beet were grown under four different irrigation regimes (fully irrigated, single drought, double drought and continually water limited) in large 610 L soil boxes in an open ended polytunnel. Measurements of leaf gas exchange, chlorophyll fluorescence and relative water content (RWC) were regularly undertaken and stomatal density, sugar and biomass yields and the associated WUE, SLW and Δ13C were assessed. The results showed that water deficits generally increase intrinsic (WUEi) and dry matter (WUEDM) water use efficiency but reduce yield. Sugar beet recovered fully after severe water deficits, as assessed by leaf gas exchange and chlorophyll fluorescence parameters and, except for reducing canopy size, showed no other acclimation to drought, and therefore no changes in WUE or drought avoidance. Spot measurements of WUEi, showed no differences between the two varieties but the prostrate variety showed lower Δ13C values, and traits associated with more water conservative phenotypes of a lower stomatal density and greater leaf RWC. Leaf chlorophyll content was affected by water deficit but the relationship with WUE was unclear. The difference in Δ13C values between the two varieties suggests traits associated with greater WUEi may be linked to canopy architecture.